LAW OF SUBSTANCE AND CONSISTENCY OF REGIONAL REGULATION NUMBER 3 OF 2006 CONCERNING COMMUNITY DEVELOPMENT ACTIVITIES IN KARIMAH - Anwar Anwar (International Journal of Islamic Khazanah, 2019)
Laying Islamic Sharia as an agenda of local government is also quite common among the people. Various institutions and activities aimed at campaigning for the "institutionalization" of Islamic Shari'a in public spaces continue to be echoed. With various weaknesses and strengths, one of which is in the district of Cianjur with the Movement for Community Development with morality, the purpose of this article is to see how the consistency of regional regulation number 3 of 2006 applies to regulations issued by the government, both regional and regent regulations, with the analytical research method. Descriptive supported by documents related to the researchers concluded that the regional regulations and the regulations of the regents have not yet optima to incorporate the morality element of karma into each Regulation that is ratified.